2020
DOI: 10.3390/healthcare8030259
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Maternal Loss: A Phenomenological Study of Older Orphans in Youth-Headed Households in Impoverished Areas of South Africa

Abstract: The aim of this study was to explore how older orphans in youth-headed households (YHHs) experience and respond to maternal death and to examine the strategies they employ to care for their younger siblings. We interviewed 18 older orphans who were purposively selected from YHHs located in informal settlements in the City of Tshwane, South Africa. After the death of their mothers, the orphans lost the family home, lost support from their relatives, lost friendships, lost educational opportunities, and lost chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…That helps me to make money that I use to survive.” This is in line with the observation by Kurebwa and Kurebwa (2014), who found that children survive by selling family property, getting assistance from childcare organizations, or resorting to dropping out of school. This is supported by Ntuli et al (2020), who states that youths heading households drop out of school to ensure they take care of their siblings.…”
Section: Resultsmentioning
confidence: 99%
“…That helps me to make money that I use to survive.” This is in line with the observation by Kurebwa and Kurebwa (2014), who found that children survive by selling family property, getting assistance from childcare organizations, or resorting to dropping out of school. This is supported by Ntuli et al (2020), who states that youths heading households drop out of school to ensure they take care of their siblings.…”
Section: Resultsmentioning
confidence: 99%
“…On SO himself, he never experienced pain while in the orphanage (Ntuli et al, 2020). According to the employee's narrative, this is related to SO's past, who was retired from the TNI so that his health is still strong and he has never been sick.…”
Section: Discussionmentioning
confidence: 99%
“…In the articles we sampled, we have found that adolescents in SADC experience psychological challenges in the form of experiencing feelings of hopelessness [38,41,42] , low self-esteem [38] anger [38,41] , and inability to deal with grief and suicidal thoughts [38,42] , shock and confusion [38,40] and they are imposed to counselling [39] , denial [40] , during the bereavement period.…”
Section: Nabunya Andmentioning
confidence: 99%
“…In terms of the social challenges, the sampled articles indicated that adolescents are unable to engage in social activities [38,42] , are stigmatised in society [38] , have poor academic performance [38,40,42] , lack support from families and friends, unable to bury their loved ones due to their age [39] . It also emerged that after the loss of the breadwinner, some of the adolescents are abused by their relatives and lack financial support [42] .…”
Section: Nabunya Andmentioning
confidence: 99%
See 1 more Smart Citation